Pathographies of Modernity with Aby Warburg and Beyond An Astral Map of Warburgian Constellations - Padularosa, Daniela 1981- (Cambridge Scholars Publishing, 2024)
The present volume aims to follow the many intersections and interferences between art history and other disciplines (such as the history of literature, theatre, cinema, photography, and dance) which can be found in Aby Warburg's writings. In particular, the volume is designed as an "astral map," whereby each chapter represents a "constellation" of polar keywords, such as Pathosformel, ancient/modern, memory, and performativity, that hark back to a Warburgian linguistic and conceptual tradition. The "word," just like the "image," polarises within itself two meanings, or rather two opposed expressive modalities. As "binary" terms, the four keywords chosen for this volume express simultaneously the vehicle of movement and the movement itself. Through the reading and contextualisation of Warburg's work, the essays presented here intend to underline the importance of the concept of "dynamic energy," in order to investigate the ability of an artwork to "move" and constantly change over time.